2022
DOI: 10.3390/antibiotics11081020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enrofloxacin on the Epiphytic Algal Communities Growing on the Leaf Surface of Vallisneria natans

Abstract: Enrofloxacin (ENR) is a member of quinolones, which are extensively used in livestock farming and aquaculture to fight various bacterial diseases, but its residues are partially transferred to surface water and affect the local aquatic ecosystem. There are many studies on the effect of ENR on the growth of a single aquatic species, but few on the level of the aquatic community. Epiphytic algae, which are organisms attached to the surface of submerged plants, play an important role in the absorption of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In the case of plants, the most common tests evaluate the effect on growing, biosorption, bioaccumulation, or toxicity. Some typically used species are: Lemna minor [84,85], Vallisneria natans [86], Lepidium sativum [87,88], and Myriophyllum spicatum [89].…”
Section: Ecotoxicological Informationmentioning
confidence: 99%
“…In the case of plants, the most common tests evaluate the effect on growing, biosorption, bioaccumulation, or toxicity. Some typically used species are: Lemna minor [84,85], Vallisneria natans [86], Lepidium sativum [87,88], and Myriophyllum spicatum [89].…”
Section: Ecotoxicological Informationmentioning
confidence: 99%
“…Xu et al [7] showed that low-dose antibiotics (sulfamethoxazole and ofloxacin) increased the root activity of Cyperus involucratus, but high-dose antibiotics (higher than 1 mg/L) produced toxic stress effects. The effects of ENR on V. spiralis also show the pattern of "low-dose-promotion and high-dose-inhibition" [14,19]. Thus, the effects of antibiotics on plants may be related to antibiotic concentrations and plant species.…”
Section: Introductionmentioning
confidence: 99%